Security cooperation in the western hemisphere : resolving the Ecuador-Peru conflict - Downes, Richard; Marcella, Gabriel (Miami, Florida : North-South Center Press at the University of Miami, 1999)
Includes bibliographical references and index
Keywords: Diplomatic negotiations in international disputes; Ecuador -- Foreign relations -- Peru; Ecuador-Peru Conflict, 1995.; Peru -- Foreign relations -- Ecuador